2015
DOI: 10.1175/jas-d-14-0201.1
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Lightning and Convective Rain Fraction in Mesoscale Convective Systems of the MJO

Abstract: Characteristics of mesoscale convective systems (MCSs) in regions affected by the Madden-Julian oscillation (MJO) are investigated using a database of MCSs observed by the Moderate Resolution Imaging Spectroradiometer (MODIS) and the Advanced Microwave Scanning Radiometer for Earth Observing System (AMSR-E). Lightning occurrence detected by the World-Wide Lightning Location Network (WWLLN) is composited in a framework centered on the MCSs. During MJO active periods, MCSs are more numerous and larger, as the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 80 publications
4
20
0
1
Order By: Relevance
“…(2016) [5]; Cheng dan Houze (1979) [6]; Schumacher dkk. (2004) [7]; Virts dan Houze (2015) [8] mengkaji bahwa di daerah tropis 40-60% curah hujan yang dihasilkan oleh MCS berasosiasi dengan daerah dengan dominasi awan stratiform. Di lintang menengah, MCS dapat berperan dalam siklus hidrologi dan secara langsung dapat berdampak terhadap peningkatan curah hujan serta berasosiasi dengan berbagai bencana hidrometeorologi seperti banjir dan longsor akibat curah hujan ekstrem yang akan mempengaruhi ketersedian bahan pangan, tanaman dan aktivitas manusia [4][5][9][10][11][12][13].…”
Section: Pendahuluanunclassified
“…(2016) [5]; Cheng dan Houze (1979) [6]; Schumacher dkk. (2004) [7]; Virts dan Houze (2015) [8] mengkaji bahwa di daerah tropis 40-60% curah hujan yang dihasilkan oleh MCS berasosiasi dengan daerah dengan dominasi awan stratiform. Di lintang menengah, MCS dapat berperan dalam siklus hidrologi dan secara langsung dapat berdampak terhadap peningkatan curah hujan serta berasosiasi dengan berbagai bencana hidrometeorologi seperti banjir dan longsor akibat curah hujan ekstrem yang akan mempengaruhi ketersedian bahan pangan, tanaman dan aktivitas manusia [4][5][9][10][11][12][13].…”
Section: Pendahuluanunclassified
“…A number of studies on MCS have been widely taken in the tropics (e.g., Mohr and Zipser 1996;Zolman and Zipser 2000;Yuan and Houze 2010;Virts and Houze 2015;Putri et al 2017Putri et al , 2018. However, research on MCS in IMC is still very limited, i.e., the general life cycle of MCS in IMC (Putri et al 2017) and the certain cases of MCS events in Sumatra and Java (Putri et al 2018) using satellite data.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that deep tropical convection is more likely associated with lightning activity (Kodama et al, ; Morita et al, ). Virts and Houze () studied the characteristics of mesoscale convective systems (MCSs) in regions affected by the Madden‐Julian Oscillation and found that during all Madden‐Julian Oscillation phases, lightning frequency decreases with distance from the center of the MCS; however, during suppressed periods, the area of enhanced lightning extends to the surroundings from the convective core. Many studies of electrical properties of MCSs have found that the stratiform regions of MCSs can be highly electrified (MacGorman et al, ; Williams et al, ).…”
Section: Introductionmentioning
confidence: 99%